Psychological Aspects of Studying the Conscious and Unconscious Components of the Cognitive Process - Abdukhalilovich, Abdurakhimov Kodirjon (International Journal of Psychosocial Rehabilitation, 2020)
At the present stage of world civilization, consciousness and the processes, which make up the cognitive aspects of our mind beginning to acquire more and more relevancy. Today, human intelligence has become a global force that drives social processes on a global scale. The cause of this phenomenon can be traced back to the fact that all the knowledge and experience in the world, words and concepts, ideas and conclusions are related to human activity. Another important fact is that by the 21st century, within the framework of the philosophical and psychological sciences, scientific studies were created and directions formed, effective methods were developed that made a definite contribution to the study of the conscious and unconscious. Particularly special attention is paid to the study of memorization, imagination, the influence of the unconscious on creativity, psychological settings in the consciousness and the unconscious and their psychophysiology, elements of cognitive reflection, stereotypes, psychological interpretation of habits and intuitions, reflection in the sensory mind, the role of unconscious intellectual functions in thinking, their manifestations as a phenomenon complementary to comprehension, the process of thinking that occurs in the subconscious.